Bioadsorben Kulit Pisang Kepok (Musa Acuminate L.) Dalam Menurunkan Kadar Timbal (Pb) Pada Larutan Pb - I Putu Krysna Anom Putra; Narwati Narwati; Pratiwi Hermiyanti; Henny Trisyanti (FORIKES, 2019)
Research has been conducted on bioadsorbent of kepok banana peel in the form of activated carbon in reducing lead levels in Pb solution. This study aims to analyze the ability of bioadsorbent kepok banana peel in reducing lead levels in Pb solution. This research was started by making bioadsorbent of Kepok banana peel in the form of 100 mesh activated carbon and activated 2.5M H2SO4. Measurement of lead levels before and after the addition of bioadsorbent of kepok banana peel using spectrophotometric methods using AAS type UV-1800 and then analyzed using One Way ANOVA test. The results showed that the average lead level before treatment was 4.96 mg / L and after being treated with additional bioadsorbent of kepok banana peel with a variation of 1 gram, 2 gram and 3 gram in sequence of 3.76 mg / L, 0.93 mg / L and 0.22 mg / L. The biggest decrease occurred in the addition of a dose of 3 grams, namely 95.6% and the lowest in the addition of a dose of 1 gram, 24.1%. One Way ANOVA test shows the results of p